2014
DOI: 10.1117/12.2044112
|View full text |Cite
|
Sign up to set email alerts
|

A cost effective and high fidelity fluoroscopy simulator using the Image-Guided Surgery Toolkit (IGSTK)

Abstract: The skills required for obtaining informative x-ray fluoroscopy images are currently acquired while trainees provide clinical care. As a consequence, trainees and patients are exposed to higher doses of radiation. Use of simulation has the potential to reduce this radiation exposure by enabling trainees to improve their skills in a safe environment prior to treating patients. We describe a low cost, high fidelity, fluoroscopy simulation system. Our system enables operators to practice their skills using the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…The study participants rated various aspects related to face and content validity and its scores, 5.28 ± 0.76 (out of 7) and 5.48 ± 0.74 respectively, compare well with validation scores of other medical training simulators. 2,5,18,22 However, as these results are based solely on the pilot study this first must be demonstrated in a larger study to more strongly support this comparison. Furthermore, it became apparent that the capabilities of the current method of simulating the fluoroscopy images need improvements.…”
Section: Discussionmentioning
confidence: 93%
“…The study participants rated various aspects related to face and content validity and its scores, 5.28 ± 0.76 (out of 7) and 5.48 ± 0.74 respectively, compare well with validation scores of other medical training simulators. 2,5,18,22 However, as these results are based solely on the pilot study this first must be demonstrated in a larger study to more strongly support this comparison. Furthermore, it became apparent that the capabilities of the current method of simulating the fluoroscopy images need improvements.…”
Section: Discussionmentioning
confidence: 93%
“…The fluoroscopy simulation of the TSP simulator was judged as very realistic with a score of 4.39 ± 0.71. Gong et al developed a dedicated fluoroscopy simulator and validated it by 11 experts answering questions on a 5‐point Likert scale. The suggested answer: “ Fluoroscopy images are realistic ” was confirmed to a mean score of 4.4 ± 0.50.…”
Section: Discussionmentioning
confidence: 99%
“…Previous solutions for C-arm fluoroscopy simulation were primarily intended for surgical training purposes. 3,4 Such systems mostly relied on external tracking systems to register the patient (or training phantom) to the coordinate system of the C-arm. Line-of-sight requirements and additional tracking hardware in the operating room (OR), including the direct cost and setup time of these systems, limit their broad utilization for the task of C-arm positioning.…”
Section: Introductionmentioning
confidence: 99%